Establishment of a TaqMan qPCR method with MGB probe for the specific detection of BVDV field strains circulating in China - An, Lele; Ren, Xiaoting; Zhang, Yetao; Zhang, Shubin; Zhao, Yongqing (Frontiers in Veterinary Science, 2025)
Bovine viral diarrhea virus (BVDV), a highly mutable pathogen, poses a significant threat to the cattle industry in China. Therefore, the development of a rapid, sensitive, and specific diagnostic assay is essential for effective surveillance and control. In this study, a TaqMan real-time quantitative PCR (qPCR) assay utilizing a minor groove binder (MGB) probe was developed for the detection of BVDV, with a focus on strains currently circulating in China. Universal primers and an MGB probe targeting the conserved 5′ untranslated region (5′UTR) of both BVDV-1 and BVDV-2 were designed based on complete genome sequences available in GenBank. Following optimization of the reaction conditions, the assay demonstrated a detection limit of 1.265 copies/μL using a plasmid standard. The method exhibited high specificity for BVDV-1 and BVDV-2, with no cross reactivity observed with other common bovine pathogens. Intra- and inter-assay coefficients of variation were below 1.5%, indicating excellent repeatability and reproducibility. When applied to field serum samples collected from free-range cattle in various regions of China, the assay achieved a 100% concordance rate with a commercial reference kit (IDEXX RealPCR™ BVDV RNA Test). These results suggest that the established TaqMan MGB qPCR assay is a reliable and efficient tool for the detection and epidemiological investigation of BVDV-1 and BVDV-2 infections in cattle herds across China.